Experimental and theoretical studies on fluvastatin primary photoproduct formation. Issue 33 (26th June 2017) - Jarmużek, Dorota; Pedzinski, Tomasz; Hoffmann, Marcin; Siodła, Tomasz; Salus, Kinga; Pluskota-Karwatka, Donata
Abstract : On the basis of transient absorption spectroscopy and DFT calculations, mechanisms of fluvastatin primary photoproduct (FP1 andFP2 ) formation were proposed. Abstract : Fluvastatin (FLV) belongs to the group of compounds referred to as statins, also known as 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors. Statins act as cholesterol-lowering agents and are among the most frequently prescribed drugs. They upregulate low-density lipoprotein receptors in the liver by binding to the active site of HMG-CoA reductase, which is the key enzyme in cholesterol biosynthesis. Statins have been detected as contaminants in natural waters and are susceptible to degradation upon exposure to light. Fluvastatin is extremely sensitive to light; upon irradiation it forms a range of photoproducts. In this study the fluvastatin molar absorption coefficient and the quantum yield of the drug photodegradation were determined. The FLV photodegradation quantum yield value determined in this work ( Φ = 0.13 ± 0.02) was found to be significantly larger than that previously reported in the literature. Our results also showed that the generation of singlet oxygen is not involved in the drug photodecomposition indicating that the excited triplet state of fluvastatin is not populated efficiently. Moreover, experimental methods and DFT calculations were applied to get insight into the possible mechanisms of fluvastatin primary photoproduct formation. Using the transient absorption spectroscopy technique, the transient species formed immediately after the drug excitation were followed, and the scheme for fluvastatin primary photochemistry was suggested. The primary photoproducts were identified on the basis of spectroscopic and spectrometric methods. A new mechanism for photooxygenation leading to the formation of one of the identified photoproducts (FP2 ) was proposed and a new approach to the formation of the other photoproduct (FP1 ) was provided. The theoretical mechanistic explanation of the photoproduct formation is in excellent agreement with the experimental data.